2017
DOI: 10.1007/s12015-017-9794-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Carrying FANCD2 Mutation Differ from the Other Fanconi Anemia Complementation Groups in Terms of TGF-β1 Production

Abstract: Transforming growth factor beta (TGF-β) secretion from cells in the bone marrow (BM) niche affects hematopoietic stem cell (HSC) fate and has a cardinal role in HSC quiescence. BM mesenchymal stem cells (BM-MSCs), a component of the BM niche, may produce abnormal levels of TGF-β in Fanconi anemia (FA) and may play a role in bone marrow failure. Here, we molecularly and cellularly characterized FA BM-MSCs by addressing their immunophenotype, proliferation- and differentiation- capacity, reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Indeed, a whole genome RNA interference (RNAi) study showed that PKNOX2 silencing increased cellular sensitivity to ionizing radiation [45]. However, our study showed that DEB treatment of BM-MSCs did not change the expression of PKNOX2 in either donor or FA patients, except one that possessed a novel deletion of exon 1-2 in FANCA gene, reported in our previous study [25]. PKNOX2 expression is lost by DEB treatment in that patient's BM-MSCs.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Indeed, a whole genome RNA interference (RNAi) study showed that PKNOX2 silencing increased cellular sensitivity to ionizing radiation [45]. However, our study showed that DEB treatment of BM-MSCs did not change the expression of PKNOX2 in either donor or FA patients, except one that possessed a novel deletion of exon 1-2 in FANCA gene, reported in our previous study [25]. PKNOX2 expression is lost by DEB treatment in that patient's BM-MSCs.…”
Section: Discussioncontrasting
confidence: 55%
“…From many (n = 1639) transcription factors found in humans [46], we focused on HOX and TALE transcription factors that are strictly under epigenetic control during adult life. TGF-β signaling interacts with HOX genes [20][21][22][23], and we previously showed fluctuation of TGF-β1 secretion from FA BM-MSCs [25]. Deregulated TGF-β signaling may disturb PKNOX2 expression in FA BM-MSCs and trigger disease progression, as seen in FA HSCs [19].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed a comprehensive comparison of MSCs derived from 18 patients with Fanconi anemia ( n = 18) and age-matched healthy controls ( n = 15) revealed increased spontaneous chromosomal fragility leading to precocious senescence and significantly reduced survival when compared to MSCs derived from age-matched healthy donors (59). These data were further confirmed in a subsequent study from Cagnan et al which documented decreased proliferation, increased ROS levels and an arrest in G2 following DEB (Diepoxybutane) treatment in MSCs from 10 Fanconi anemia patients, with especially absent transforming growth factor (TGF)- β secretion and elevated senescence levels in the FANCD2 mutated cases (60). Analysis of MSCs from Shwachman-Diamond syndrome (SDS) patients, another major subgroup of congenital BMF, also revealed profound functional defects and failed to recreate a BM niche in an in vivo heterotopic ossicle model (61).…”
Section: The Bone Marrow Microenvironment In Aamentioning
confidence: 58%